Adaptability analysis of solar water heating system in Chongqing area. Issue 1 (March 2021) - Ma, Xiaoxue; Wang, Xiaotong; Meng, Fanlin
Abstract: According to the simulation software TRNSYS, based on meteorological parameters and and the distribution of solar energy resources in Chongqing area, the dynamic simulation method is used to analyze the application effect of the solar water heating system in Chongqing area. The results show that the application of solar water heating system in Chongqing area has potential, but it has obvious seasonal characteristics, with sufficient solar radiation in summer, followed by spring and autumn, and the least in winter. The simulation calculation shows that the monthly thermal efficiency of the collector fluctuates between 0.2 and 0.7 throughout the year, with an average value of 0.51. The solar fraction basically increases with the increase of solar radiation, which also has obvious seasonal characteristics.